Human metapneumovirus infection activates the TSLP pathway that drives excessive pulmonary inflammation and viral replication in mice. Issue 6 (15th April 2015) - Lay, Margarita K.; Céspedes, Pablo F.; Palavecino, Christian E.; León, Miguel A.; Díaz, Rodrigo A.; Salazar, Francisco J.; Méndez, Gonzalo P.; Bueno, Susan M.; Kalergis, Alexis M.
<x xml:space="preserve">Abstract</x> Human metapneumovirus (hMPV) is a leading cause of acute respiratory tract infections in children and the elderly. The mechanism by which this virus triggers an inflammatory response still remains unknown. Here, we evaluated whether the thymic stromal lymphopoietin (TSLP) pathway contributes to lung inflammation upon hMPV infection. We found that hMPV infection promotes TSLP expression both in human airway epithelial cells and in the mouse lung. hMPV infection induced lung infiltration of OX40L+CD11b+ DCs. Mice lacking the TSLP receptor deficient mice (tslpr−/−) showed reduced lung inflammation and hMPV replication. These mice displayed a decreased number of neutrophils as well a reduction in levels of thymus and activation‐regulated chemokine/CCL17, IL‐5, IL‐13, and TNF‐α in the airways upon hMPV infection. Furthermore, a higher frequency of CD4+ and CD8+ T cells was found in tslpr−/− mice compared to WT mice, which could contribute to controlling viral spread. Depletion of neutrophils in WT and tslpr−/− mice decreased inflammation and hMPV replication. Remarkably, blockage of TSLP or OX40L with specific Abs reduced lung inflammation and viral replication following hMPV challenge in mice. Altogether, these results suggest that activation of the TSLP pathway is pivotal in the development of pulmonary pathology and pulmonary hMPV replication.